How to build confidence and become more assertive (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. Assertiveness means standing your ground, being transparent about your feelings and communicating your boundaries. By the end of this lesson, you will understand why assertiveness matters and how it can enhance your life and be familiar with some practical methods for developing it. Many people struggle to be assertive because they are concerned about upsetting someone else's feelings. It sometimes feels easier to stay quiet and avoid conflict. We'll guide you through managing these worries, establishing boundaries, and asking for what you need. In this lesson, you will discover that assertiveness isn't about creating conflict or controlling others. It's not about instilling fear or denying responsibility. We'll provide real-life examples to give you a solid foundation for developing confidence and standing up for your beliefs. Learning Objectives Establish how to find inner confidence and become more assertive. Examine a range of skills for improving assertiveness. Discover the distinction between aggressiveness and assertiveness.